The effects of child encounters during military deployments on the well-being of military personnel: a systematic review. Issue 2 (19th December 2022) - Ein, Natalie; Liu, Jenny J. W.; Houle, Stephanie A.; Easterbrook, Bethany; Turner, Richard Benjamin; MacDonald, Caleb; Reeves, Kathryn; Deda, Erisa; Hoffer, Ken; Abidi, Catherine Baillie; Nazarov, Anthony; Richardson, J. Don
ABSTRACT: Background: Military members report higher instances of trauma exposure and subsequent posttraumatic stress disorder (PTSD) relative to civilians. Encounters with children in war and conflict settings may have particularly unsettling consequences. However, the nature of these consequences has yet to be systematically examined. Objective: This systematic review sought to identify and document deployment-related encounters with children and associated outcomes reported by military personnel, as well as identify any current training programs, policies, or procedures in place regarding encountering children during deployment. Method: A total of 17 studies with 86 independent samples were included. Analyses were based primarily on qualitative data. Results: Based on the review, 77 military personnel samples documented their experiences encountering children during deployment. Most commonly, child encounters included armed children, porters/human shields, suicide bombers, and ambiguous interactions. Outcomes from encountering children during deployment were diverse, occurring both during the encounter, and described by many as persisting years following the exposure. Consequences of encounters as described by military personnel included: hesitation to complete mission objectives, mental health concerns, moral struggles, social isolation, and sleep disturbances. Of the 86 included reports, only nine provided information regarding training at any stage (pre-, during, or post-deployment) in relation to encountering children. Much of the available information underscored the lack of training, with six reports highlighting the lack of pre-deployment training and five reports describing the lack of policies, including rules of engagement, as they relate to encountering children during deployment. Only two reports described post-deployment procedures made available to military personnel following exposure to children while on deployment. Conclusions: Results from this review will be used to identify available research, develop and support training initiatives, and increase awareness regarding implications of encountering children during deployment. We further provide recommendations regarding research needs, policy implementation, and current training gaps. HIGHLIGHTS: A systematic review that identified and documented deployment-related encounters with children and associated outcomes reported by military personnel, as well as identified current training programs, policies, or procedures in place regarding encountering children during deployment. The review found child encounters included armed children, porters/human shields, suicide bombers and ambiguous interactions with consequences, described by military personnel, of mental health concerns, moral struggles (e.g. loss of faith), sleep disturbances, social isolation, and inability to work. Available data showcased a lack of training, lack of policies, and lack of post-deployment interventions.